Conventional magnetic resonance imaging combined with three-dimensional ultrasound for preoperative prediction of immediate ablation rate in high-intensity focused ultrasound treatment of uterine fibroids - Qiong Hao; Junwei Liu; Ruoying Hou; Wenxia Huang; Juan Liao; Zhenjiang Lin; Tijiang Zhang (International Journal of Hyperthermia)
Objective This study aimed to assess the effectiveness of conventional magnetic resonance imaging (MRI) combined with three-dimensional (3D) ultrasound for the preoperative prediction of nonperfused volume ratio (NPVR) in uterine fibroids after high-intensity focused ultrasound (HIFU) ablation.Materials and methods In total, 178 patients who had undergone HIFU ablation therapy for uterine fibroids between July 2021 and August 2023 were enrolled. Baseline clinical, MRI, and 3D ultrasound parameters collected before and after HIFU ablation were analyzed. Multiple linear regression models were constructed for conventional MRI parameters alone and for combined MRI–3D ultrasound parameters to predict NPVR. Paired-sample t-tests and Pearson’s correlation were employed to assess relationships between predicted and actual NPVR values. The prediction efficacy of both models was statistically compared.Results The combined MRI–3D ultrasound model outperformed the conventional MRI model, with adjusted R2 values of 0.597 and 0.553, respectively, both statistically significant (p < 0.05). The combined model revealed that signal intensity on T2-weighted imaging, degree of enhancement on contrast-enhanced T1-weighted imaging, maximum distance between the fibroid’s dorsal surface and the skin, uterine fibroid vascular network, and fibroid vascularization negatively affected NPVR. The predicted NPVR was significantly correlated with the actual NPVR (p < 0.001).Conclusions 3D ultrasound provided essential information for screening fibroids and predicting NPVR before HIFU ablation, serving as a valuable supplement to MRI. The combined MRI–3D ultrasound model shows promise for the preoperative prediction of NPVR in patients with uterine fibroids treated with HIFU and may offer substantial clinical value.